2019
DOI: 10.1111/jpn.13102
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on the association with feeding and recovery length in equine colic patients after laparotomy

Abstract: Colic is a serious disease for horses and the nutritional management of postoperative colic patients is an extremely important field. The aim of this retrospective study was to analyse the different factors, especially related to nutritional management, that may be associated with recovery length during hospitalization after a surgical intervention for colic, using a multivariate model. Data were collected from the records of horses presented to two hospitals and undergoing surgery for colic. The length (days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The positive effects of EN in recovery and survival for the post‐operative colic have for the majority been extrapolated from the human literature 3‐7 and discussed within the referenced textbooks 8,15 . In a small single‐centre study of 37 horses, Valle et al (2019) identified an association with feeding and recovery time in equine colic cases after laparotomy 19 . Those that were consuming forage within 12 hours post‐operatively had a shorter recovery time 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effects of EN in recovery and survival for the post‐operative colic have for the majority been extrapolated from the human literature 3‐7 and discussed within the referenced textbooks 8,15 . In a small single‐centre study of 37 horses, Valle et al (2019) identified an association with feeding and recovery time in equine colic cases after laparotomy 19 . Those that were consuming forage within 12 hours post‐operatively had a shorter recovery time 19 .…”
Section: Discussionmentioning
confidence: 99%
“…8 , 15 In a small single‐centre study of 37 horses, Valle et al (2019) identified an association with feeding and recovery time in equine colic cases after laparotomy. 19 Those that were consuming forage within 12 hours post‐operatively had a shorter recovery time. 19 Although the authors recognise the fact that horses that recover swiftly after surgery are likely to be offered EN faster than those that recover more slowly, they also suggest that EN can positively affect intestinal motility and enterocyte function to provide a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless food intake should be encouraged in the postoperative period to stimulate gut motility and, in selected cases, to prevent hypertriglyceridemia, eliminate the need for parenteral nutrition, 24,25 and to promote water intake. In fact, Freeman et al 2 observed that unfed horses drink significantly less than fed horses.…”
Section: Discussionmentioning
confidence: 99%
“…8,21 Excluding the two horses for which a possible explanation of POR has been provided above, the incidence of true POI in our study was 10%, in accordance with the findings reported by Freeman et al 22 All horses that developed POR in our study had some degree of gastric impaction, revealed by direct palpation at surgery, as reported by others concurrently to other forms of colic. 23 Thus, in addition to the anastomotic technique and intestinal oedema, gastric contents could move from the stomach and Nevertheless food intake should be encouraged in the postoperative period to stimulate gut motility and, in selected cases, to prevent hypertriglyceridemia, eliminate the need for parenteral nutrition, 24,25 and to promote water intake. In fact, Freeman et al 2 observed that unfed horses drink significantly less than fed horses.…”
Section: Discussionmentioning
confidence: 99%